Biology of childhood germ cell tumours, focussing on the significance of microRNAs. (9th October 2014) - Murray, M. J.; Nicholson, J. C.; Coleman, N.
Summary: Genomic and protein‐coding transcriptomic data have suggested that germ cell tumours (GCTs) of childhood are biologically distinct from those of adulthood. Global messenger RNA profiles segregate malignant GCTs primarily by histology, but then also by age, with numerous transcripts showing age‐related differential expression. Such differences are likely to account for the heterogeneous clinico‐pathological behaviour of paediatric and adult malignant GCTs. In contrast, as global microRNA signatures of human tumours reflect their developmental lineage, we hypothesized that microRNA profiles would identify common biological abnormalities in all malignant GCTs owing to their presumed shared origin from primordial germ cells. MicroRNAs are short, non‐protein‐coding RNAs that regulate gene expression via translational repression and/or mRNA degradation. We showed that all malignant GCTs over‐express the miR‐371–373 and miR‐302/367 clusters, regardless of patient age, histological subtype or anatomical tumour site. Furthermore, bioinformatic approaches and subsequent Gene Ontology analysis revealed that these two over‐expressed microRNAs clusters co‐ordinately down‐regulated genes involved in biologically significant pathways in malignant GCTs. The translational potential of this finding has been demonstrated with the detection of elevated serum levels of miR‐371–373 and miR‐302/367 microRNAs at the time of malignant GCT diagnosis, with levels falling after treatment. The tumour‐suppressor let‐7 microRNA family has also been shown to be universally down‐regulated in malignant GCTs, because of abundant expression of the regulatory gene LIN28 . Low let‐7 levels resulted in up‐regulation of oncogenes including MYCN, AURKB and LIN28 itself, the latter through a direct feedback mechanism. Targeting LIN28, or restoring let‐7 levels, both led to effective inhibition of this pathway. In summary, paediatric malignant GCTs show biological differences from their adult counterparts at a genomic and protein‐coding transcriptome level, whereas they both display very similar microRNA expression profiles. These similarities and differences may be exploited for diagnostic and/or therapeutic purposes.